DAMPAK PENYULUHAN JAJANAN SEHAT TERHADAP PENGETAHUAN DAN SIKAP ANAK SEKOLAH DASAR DI MADRASAH IBTIDAIYAH AL-FITRAH KAMPUNG NELAYAN OESAPA KUPANG - Astuti Nur (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
ABSTRACT One aspect that plays an important role in providing energy and nutritional intake and maintaining learning resilience for children while in school is snack food. BPOM survey results show that for 6-8 hours per day the child's time is spent in school and 90 percent of school children buy snacks at school. The snacks purchased are not yet known for their safety and cleaning, so you need a specific strategy to find out how to choose healthy snacks. This study aims to determine the impact of healthy snacks education of the knowledge and attitudes of the students at Madrasah Ibtidaiyah Al-Fitrah Fishermen's Village of Oesapa Kupang. This research used quasy experiment with one group pre test and post test design. The sample of this experiment was the V grades of Madrasah Ibtidaiyah Al-Fitrah. The sample was 61 respondents that got education about healthy snacks. Data take from the questionnaire pre test and post test after the education. Data analyze used paired sample t test. The results showed an increase in the value of the subject's knowledge and attitudes after educated which was then statistically analyzed, the increase that occurred was significant 0,000 (p <0.05). This shows that education about healthy snacks has an impact that is increasing the knowledge and attitude of the subject. Keywords: Education, Healthy Snack, Knowledge, Attitude